Hormone-Integrin Cross Talk and Angiogenesis Modulation - Mousa, Shaker A.; Davis, Faith B.; Davis, Paul J. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2009)
Angiogenesis is regulated by a number of endogenous stimulators and inhibitors and involves multiple biological steps, including endothelial cell proliferation, cell migration, cell-cell and cell-matrix adhesion and assembly into tube structures. Designing and developing peptides or non-peptide mimetics for therapeutic application to stimulate or inhibit angiogenesis is an important current area in drug development. Information coded in endogenous protein angiogenesis stimulators and inhibitors hold is important to the design of anti-angiogenesis peptides and, ultimately, non-peptide mimetic. Several hormones affect angiogenesis via their interactions with extracellular matrix molecules, cell surface receptors and proteases, as well as growth factors and cytokines. Recent reports have ascribed pro-angiogenic activity to several thyroid hormone analogues, including Lthyroxine (T4), 3,5,3'-triiodo-L-thyronine (T3) and diiodothyropropionic acid (DITPA). Model systems of angiogenesis have demonstrated that thyroid hormone-induced neovascularization is initiated at a cell surface integrin receptor. The hormone signal is transduced within the cell by cell surface integrin-extracellular matrix regulated kinase 1/2 (ERK1/2), leading to secretion of basic fibroblast growth factor (bFGF) and other growth factors and resulting in angiogenesis. Studies in intact animal have shown that endogenous or exogenous thyroid hormone supports blood vessel density in heart, brain and ischemic limbs. Additionally, other steroid hormones and insulin-glucose homeostasis play key roles in modulating angiogenesis. This review will highlight several hormonal systems that affect angiogenesis, but will focus largely on the thyroid hormone-integrin interaction that affects neovascularization.